Histones: The critical players in innate immunity - Li, Xia; Ye, Youyuan; Peng, Kailan; Zeng, Zhuo; Chen, Li; Zeng, Yanhua (Frontiers in Immunology, 2022)
The highly conserved histones in different species seem to represent a very ancient and universal innate host defense system against microorganisms in the biological world. Histones are the essential part of nuclear matter and act as a control switch for DNA transcription. However, histones are also found in the cytoplasm, cell membranes, and extracellular fluid, where they function as host defenses and promote inflammatory responses. In some cases, extracellular histones can act as damage-associated molecular patterns (DAMPs) and bind to pattern recognition receptors (PRRs), thereby triggering innate immune responses and causing initial organ damage. Histones and their fragments serve as antimicrobial peptides (AMPs) to directly eliminate bacteria, viruses, fungi, and parasites in vitro and in vivo. Histones are also involved in phagocytes-related innate immune response as components of neutrophil extracellular traps (NETs), neutrophil activators, and plasminogen receptors. In addition, as a considerable part of epigenetic regulation, histone modifications play a vital role in regulating the innate immune response and expression of corresponding defense genes. Here, we review the regulatory role of histones in innate immune response, which provides a new strategy for the development of antibiotics and the use of histones as therapeutic targets for inflammatory diseases, sepsis, autoimmune diseases, and COVID-19.